Permainan Money Monopoly sebagai Media Meningkatkan Literasi Keuangan pada Anak Autis - Verdian, Ristania Harwin; Sujarwanto, Sujarwanto; Widjati, Wiwik; Widiastuti, Erna (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This study aims to enhance the financial literacy skills of autistic students through the use of the educational game Moly. The Moly application is designed as an interactive and engaging Money Monopoly game to help autistic children understand financial concepts, recognize currency denominations, conduct transactions, and manage money in everyday situations. This study employs a Classroom Action Research (CAR) method with two cycles, each consisting of two actions. The sample consists of 6 autistic students at SDLB SLBN Seduri Mojokerto. The results show a significant increase in the financial literacy skills of the students, with the average score rising from 40% in the pretest to 81% in the posttest. Observations during the learning process also indicate increased participation and positive interactions among the students. This improvement reflects the effectiveness of the Moly application in enhancing financial literacy and social skills of autistic students.